Measurement of the top quark forward-backward production asymmetry and the anomalous chromoelectric and chromomagnetic moments in in pp collisions at root s=13 TeV - Sirunyan, A. M. (2020)
The parton-level top quark (t) forward-backward asymmetry and the anomalous chromoelectric ((d) over cap (t)) and chromomagnetic ((mu) over capt) moments have been measured using LHC pp collisions at a center-of-mass energy of 13TeV, collected in the CMS detector in a data sample corresponding to an integrated luminosity of 35.9 fb(-1) The linearized variable A(FB)((1)) is used to approximate the asymmetry. Candidate t (t) over bar events decaying to a muon or electron and jets in final states with low and high Lorentz boosts are selected and reconstructed using a fit of the kinematic distributions of the decay products to those expected for t (t) over bar final states. The values found for the parameters are A(FB)((1)) = 0.048(-0.087)(+0.095)(stat)(-0.029)(+0.020) (syst), (mu) over cap (t) = 0.024(-0.009)(+0.013) (stat)(-0.011)(+0.016) (syst), and a limit is placed on the magnitude of vertical bar(d) over cap (t)vertical bar < 0.03 at 95% confidence level.